IMPROVING TOURISM EXPERIENCE AT PROMTHEP CAPE IN PHUKET THAILAND THROUGH THE ROLES OF TOUR GUIDES - Sarwono, Aldi Wisnumurti; Vionita, Monica (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Promthep Cape is one of the well known nature tourist attractions in Phuket, Thailand. One of its attractions offers the beauty of nature that tourists can enjoy, especially during sunset. Another attraction is the existence of a temple of which tourists can use to make offerings to Lord Brahma. Regardles these and many more interesting attractions, Prompthep Cape is still laking of information regarding the explanation of those attractions. Most visitors could not get the narratives about the history, the culture, and other required narratives of Promthep Cape as a popular nature tourism. This will lead to the decrease of tourism experience when visiting Prompthep Cape. One source of information that tourists can get is from a tour guide who accompanies them when visiting Promthep Cape. This study tries to answer the question why a tour guide is needed to improve the experience of tourists visiting Promthep Cape, and what are the roles of the tour guide in improving the tourism experience visiting Prompthep Cape. The method used is descriptive qualitative by utilizing primary data from observations and interviews, as well as secondary data in the form of related documents. The data is then reduced, interpreted, and analyzed. Results show that a tour guide has 4 roles in improving the experience of tourists visiting Promthep Cape, namely: 1) to increase the tourist knowledge of the destination, 2) to give more meaning in traveling, 3) to provide a sense of security and comfort to tourists, and 4) to act as a translator for foreign tourists, especially those with language limitations.